Технічні канали витоку мовної інформації за рахунок засобів дистанційної акустичної розвідки - Льозіна, О. О. (ХНУРЕ, 2024)
With the development of information influence, there are requirements for saving information from leaking. Thesis is about the problems of information leakage through acoustic channels. Devices for listening information are described. Special attention is paid to the various microphones. As a result, the methods of combating information leakage are indicated.
Keywords: виток мовної інформації; дистанційна акустична розвідка